2004
DOI: 10.1176/appi.ajp.161.6.1038
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Glucose Metabolism in Obsessive-Compulsive Hoarding

Abstract: OCD patients with the compulsive hoarding syndrome had a different pattern of cerebral glucose metabolism than nonhoarding OCD patients and comparison subjects. Obsessive-compulsive hoarding may be a neurobiologically distinct subgroup or variant of OCD whose symptoms and poor response to anti-obsessional treatment are mediated by lower activity in the cingulate cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
177
3
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(202 citation statements)
references
References 88 publications
(91 reference statements)
14
177
3
5
Order By: Relevance
“…Interestingly, in the resting state PET study by Saxena et al, 14 the severity of compulsive hoarding also correlated with increased metabolism in sensorimotor cortex. This brain region has a crucial role in the visual processing of emotional material.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Interestingly, in the resting state PET study by Saxena et al, 14 the severity of compulsive hoarding also correlated with increased metabolism in sensorimotor cortex. This brain region has a crucial role in the visual processing of emotional material.…”
Section: Discussionmentioning
confidence: 90%
“…Saxena et al 14 found that 12 OCD patients with predominant hoarding symptoms showed reduced glucose metabolism in the dorsal anterior cingulate cortex and increased metabolism in the right sensorimotor cortex, compared with 33 non-hoarding OCD patients. In addition, across all OCD patients (n = 45), the severity of hoarding was negatively correlated with metabolism in the former region and positively correlated with metabolism in the latter region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients completed a measure of depression and anxiety levels using Beck Depression Inventory (BDI) (Beck et al, 1961) and Beck Anxiety Inventory (BAI) (Beck et al, 1988), respectively. We classified the OCD patients according to the five clinical dimensions (Mataix-Cols et al, 1999) and excluded patients with hoarding symptoms due to their different neural involvement from non-hoarding OCD patients (Lochner et al, 2005, Saxena et al, 2004. Predominant obsession/compulsions were as follows: contamination/cleaning (N = 9), aggressive/checking (N = 3), miscellaneous (N = 6), and symmetry/ordering (N = 2).…”
Section: Participantsmentioning
confidence: 99%
“…14,15 In one factor analytic study of neuropsychological functioning, three major subsets of patients were observed with differential patterns of association between OCS subtypes and performance on the WCST and Part B of the Trail Making Test. 16 One subset of patients was impaired on both tests and had prominent contamination obsessions and compulsive washing.…”
mentioning
confidence: 99%